Socio-economic and Demographic Determinants of Antenatal Care Services Utilization in Central Nepal - Srijana Pandey, PhD; Supendra Karki, MPH, MA (Global Health and Education Projects, Inc., 2015)
Background/Objective: The importance of maternal health services in lessening maternal mortality and morbidity as well as neonatal deaths has received substantial recognition in the past decade. The lack of antenatal care has been identified as a risk factor for maternal mortality and other adverse pregnancy outcomes. The purpose of this study was to determine the factors affecting attendance of antenatal care services in Nepal. Methods: This is a cross-sectional descriptive study carried out in Central Nepal. Using semi-structured questionnaire, interviews were conducted with married women aged between 15-49 years, who had delivered their babies within one year. Systematic random sampling method was used to select the sample. Results were obtained by frequency distribution and cross-tabulation of the variables. Results: More than half of the women were not aware of the consequences of lack of antenatal care. Age, education, income, type of family were strongly associated with the attendance at antenatal care service. Conclusions and Public Health Implications: In Nepal and in other developing countries, maternal mortality and morbidity continue to pose challenges to the health care delivery system. Variety of factors including socio-demographic, socio-economic, cultural and service availability as well as accessibility influences the use of maternal health services. Key words: Antenatal care • Maternal health services • Antenatal care services • Nepal Copyright: © 2014 Pandey et al. This is an open-access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited.